Sensing Senses: Tactile Feedback for the Prevention of Decubitus Ulcers - Verbunt, Marcel (Springer US, 2009)
Decubitus ulcers, also known as pressure sores, is a major problem in health care, in particular for patients with spinal cord injuries. These patients cannot feel the discomfort that would urge healthy people to change their posture. We describe a system that uses a sensor mat to detect problematic postures and provides tactile feedback to the user. The results of our preliminary study with healthy subjects show that the tactile feedback is a viable option to spoken feedback. We envision the system being used for rehabilitation games, but also for everyday Decubitus ulcers prevention.